1883 Wis. Sess. Laws 990, ch. 341, § 52, pt. 40 - (:unkn) unknown (My University, 1883)
Authorized the city to prohibit and prevent the carry of any pistol, Bowie-knife, dirk, dagger, or other concealed and dangerous weapon, except as authorized by law.
Keywords: CARRY - CONCEALED